The purportedly Indo-Australian gecko species Cnemaspis timoriensis (Duméril & Bibron, 1836) is actually the first named species of the neotropical genus Gonatodes Fitzinger, 1843 (Squamata: Gekkonidae) - Rösler, Herbert; Grismer, L. Lee; Ineich, Ivan; Kaiser, Hinrich (Zootaxa, 2019)
Only a single known specimen of Cnemaspis timoriensis (Duméril & Bibron, 1836) exists, the holotype in the Muséum National d’Histoire Naturelle in Paris, France. Purportedly collected by Charles Gaudichaud-Beaupré in the year 1818 on Timor Island in the Lesser Sunda Archipelago during the circumnavigation of the globe by the vessel L’Uranie, intensive research on Timor has failed to produce additional specimens or any similarly appointed gecko. Using a series of detailed morphological comparisons, we provide irrefutable evidence that the animal in question is not a member of Cnemaspis but of the neotropical genus Gonatodes. Furthermore, we ascertained that C. timoriensis is conspecific with G. humeralis, a widely distributed South American species. We also show that a specimen labeled with the timoriensis name in the Museum für Naturkunde, Berlin, Germany is not conspecific and not part of a type series. While the taxon name timoriensis has nomenclatural priority over the two-decades-younger name humeralis, usage would dictate that to preserve the nomenclatural stability of neotropical geckos the junior synonym should be retained. An application to the International Commission on Zoological Nomenclature to this effect is in preparation.